Medication Error Incidence (Parenteral Therapy) at Government Hospital in Magelang - Setiarta, Daniswara; Huriah, Titih (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Patient safety is the key to maintain the quality of health services. One of the most important things to achievepatient safety is to identify medication errors and its causes. Most cases of medication errors are reported bynurses, because nurses are the therapeutic team. The purpose of this study is to determine factors affectingmedication error by nurse in giving parenteral therapy at Government Hospital in Magelang. A cross-sectionalanalytic study was carried out on 67 nurses working in hospital wards. The data were collected using aquestionnaire filled by respondents to see medication errors within 3 months. The final number of medicationerrors were 91 incidents in 3 months. The most frequent errors were wrong time (51.7%), wrong dose (14.2%),wrong document and wrong drug (9.9%), wrong route (8.8%), and the least was wrong patient (5%). Althoughthe medication error incidences were not sentinel events and didn’t affect to SNARs criteria, but it still affectingon the quality of health services in the hospital. The significant independent determinant of medication errors isworking experience at Government Hospital in Magelang (p 0,001), while the other determinants are not.Conclusion in this study was significant correlation between work experience in hospital and medication error,where respondents with work experience at Government Hospital in Magelangless than 5 years tend to be athigher risk doing medication errors than those who having worked more or equivalent to 5 years.